Primary cardiac angiosarcoma causing rupture of the heart and spontaneous bilateral pneumothorax. - Lobo, A J (1989)
A patient with a primary cardiac angiosarcoma developed two previously unreported manifestations: cardiac rupture, which has not been reported with any primary cardiac tumour; and spontaneous pneumothorax, which is well recognised with other tumours but has not been reported with a cardiac angiosarcoma.